ANALSIS POLA ASUH ORANG TUA PADA KELUARGA BROKEN HOME TERHADAP TINGKAT KEPERCAYAAN DIRI ANAK DI SDN 2 MAJIDI KECAMATAN SELONG - Ika Rahmayanti; M. Deni Siregar; Hadiatul Rodiyah; Habibuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze in depth the parenting styles applied by parents in broken home families and their impact on children's self-confidence. Broken home phenomena have been increasing and have significant implications for children's psychological development, particularly in the area of self-confidence, which is a key factor in academic and social success. The research employed a descriptive qualitative approach using a case study design at SDN 2 Majidi. The participants consisted of two children from broken home families, their parents, and teachers as supporting informants. Data were gathered through in-depth interviews, direct observations, and documentation of children's daily activities and interactions with parents and teachers. Data analysis was carried out using Miles & Huberman's interactive model, which involves data reduction, data display, and conclusion drawing. The validity of the data was checked using triangulation of sources and techniques to ensure credibility and reliability of the findings. The results indicate two dominant parenting styles in broken home families, namely permissive and authoritarian. Children raised with permissive parenting often experience low self- confidence due to a lack of guidance, supervision, and emotional support. On the other hand, children raised under authoritarian parenting also display low self- confidence as a result of emotional pressure, strict control, and limited opportunities to express themselves freely. This study highlights the importance of parents adopting a democratic parenting style that provides balanced support and guidance. In addition, schools and teachers play a crucial role in providing counseling, emotional support, and motivation to children from broken home families. The findings of this research have implications for the development of parent training programs and school-based interventions aimed at fostering a supportive environment that enhances children'sself-confidence.